EDD 701: Diversity, Equity, Inclusion, Accessibility & Justice in Education
This course is designed to engage students in reflection and critique of theoretical approaches dealing with cross-cultural education that promote equity and social justice within educational settings and society. Using diverse and conflicting perspectives, students will gain a greater understanding of challenges and opportunities that align theory and practice with a focus on diversity, equity, inclusion, accessibility, and justice. Students will engage in personal examination of the complexity of views and perceptions as educational leaders in super diverse societies.